The Role Of The Microflora And Microfauna Communities In The Production Of Udang Galah (Macrobrachium Rosenbergii (De Man) Juveniles Using The 'Modified Static "Green-Water" System' - Ng, Chee Kiat (1995)

(untitled)
The modified static " green-water " system ' for the production of udang galah juveniles was developed by Ang and Cheah (1986) .However , studies on the microbial community are scant . There fore , experiments were conducted to study the functioning of the 'modified static " green-water " system ' with respect to the microflora and microfauna community and the effect of light intensity on the system.Four series of experiments were conducted at various light intensities to study the effect of light intensity on the system with respect to community structure . Experiments were conducted for the duration of the larviculture period which ranged from 20 to 25 days . Results were compared using Morosita's index of similarity .